Knockdown of USP14 inhibits PDGF-BB-induced vascular smooth muscle cell dedifferentiation via inhibiting mTOR/P70S6K signaling pathway. Issue 63 (11th November 2019) - Liu, Hongbin; Li, Xiaoliang; Yan, Guobei; Lun, Ruihua
Abstract : Atherosclerosis is a chronic progressive cardiovascular disease, which may result in many clinical consequences. Abstract : Atherosclerosis is a chronic progressive cardiovascular disease, which may result in many clinical consequences. Ubiquitin-specific protease 14 (USP14), a member of the USP family, has been found to be involved in cardiovascular disease. In the present study, we aimed to explore the role of USP14 in atherosclerosis. The results showed that USP14 expression was markedly increased in atherosclerotic tissues as compared to control tissues. Then we next examined the role of USP14 in primary human aortic smooth muscle cells (HASMCs) in response to PDGF-BB stimulation. The results demonstrated that PDGF-BB induced the USP14 expression in a dose- and time-dependent manner. Knockdown of USP14 in HASMCs suppressed PDGF-BB-induced proliferation and migration of HASMCs. The expressions of VSMCs markers including α-SMA, calponin and SM-MHC were markedly increased by knockdown of USP14, indicating that USP14 knockdown suppressed phenotypic modulation of HASMCs. However, USP14 overexpression exhibited the opposite effects. Furthermore, PDGF-BB-induced phosphorylation of mTOR and P70S6K in HASMCs was prevented by knockdown of USP14. In addition, MHY-1485, an activator of mTOR signaling, reversed the effects of USP14 knockdown on PDGF-BB-induced HASMCs. These data suggested that knockdown of USP14 prevented PDGF-BB-induced proliferation, migration, and phenotypic modulation of HASMCs via inhibiting the mTOR/P70S6K signaling pathway.